The construction of the Miguel Delibes´s Archive. The plan of creation - Ortega Álvarez, Javier (Revista General de Información y Documentación, 2024)
In this work, as stated in its title, we show the process of identification and organization of the documents of the documentary legacy of the writer Miguel Delibes; in short, the process of construction of the Miguel Delibes Archive, so that the different phases of the writer's creative process can be discovered through the documents in the archive and the documentary relationships established between them.
Keywords: Miguel Delibes Archive; identification; description; organization; creative process